Mendelian randomization indicates a causal contribution of type 2 diabetes to retinal vein occlusion - Huang, Jian (Frontiers in Endocrinology, 2023)
Background: Retinal vein occlusion (RVO) is a common retinal vascular disease that can cause severe visual impairment. Many observational studies have shown that type 2 diabetes (T2DM) is associated with RVO, but it remains unknown if the association is causal. The present study aimed to perform Mendelian randomization (MR) analyses to evaluate the causal contribution of genetically predicted T2DM to RVO. Methods: We obtained summary-level data from a genome-wide association study meta-analysis including 48,286 cases and 250,671 controls for T2DM and from a genome wide association study of 372 cases and 182,573 controls in the FinnGen project for RVO. To verify the robustness of the results, an independent validation dataset for T2DM (12,931 cases and 57,196 controls) was used. In addition to the main MR analysis using the inverse variance weighted (fixed effect) approach, sensitivity analyses and multivariable MR adjusting for common risk factors of RVO were conducted. Results: Genetically predicted T2DM was found to be causally associated with RVO risk (odds ratio (OR)=2.823, 95% confidence interval (CI): 2.072-3.847, P=4.868×10-11). This association was supported by sensitivity analyses using the weighted median (OR=2.415, 95% CI: 1.411-4.132, P=1.294×10-3), weighted mode (OR=2.370, 95% CI: 1.321-4.252, P=5.159×10-3), maximum likelihood (OR=2.871, 95% CI: 2.100-3.924, P=3.719×10-11), MR-PRESSO (OR=2.823, 95% CI: 2.135-3.733, P=5.150×10-10), and MR-Egger (OR=2.441, 95% CI: 1.149-5.184, P=2.335×10-2) methods. In addition, this association persisted in multivariable MR after accounting for common RVO risk factors (OR=1.748, 95% CI: 1.238-2.467, P=1.490×10-3). The MR analyses using the validation dataset obtained consistent results. Conclusion: This study indicates that genetically predicted T2DM may have a causal contribution to RVO. Future studies are required to elucidate the underlying mechanisms.